THE SUNDANESE ECO-RELIGION KAMPONG OF KASEPUHAN CIPTAGELAR INDIGENOUS LOCAL COMMUNITY: CASE STUDY KAMPONG CENGKUK, SUKABUMI REGENCY - Ary Sulistyo (Pusat Penelitian Arkeologi Nasional, 2020)
Abstract. This research focused on eco-religion of indigenous Sundanese local community of Kasepuhan Ciptagelar at Southern Halimun Mountain on how to manage sustainable environment. The Kampong Cengkuk is one of several kampongs that still follow the tradition of indigenous local community of Kasepuhan Ciptagelar for hundred years. This descriptive qualitative research aims to reveal the internal and external factors led to deforestation of natural forests with average around 6-8% per year. The research shows that the kampong is still practicing eco-religion tradition by protecting forestland (leuweung tutupan) only for their subsistence. The hypothesis is that the social-culture changes had been occurred in the community not only to restrict outer island agriculture in the forest, but also, in wet rice cultivation activities, to manage sustainable environment. The reduction in process and ceremonial activities also happened, which was originally eight ceremonies of outer island agriculture rituals into five ceremonies of wet rice cultivation. The more profane activities were developing economic crops in home garden. Keywords: Ecoreligion, Kampong, Environment, Forest, Tradition Abstrak. Penelitian ini membahas tentang eko-religi masyarakat lokal Sunda Kampung Ciptagelar di Pegunungan Halimun Selatan bagaimana dalam pengelolaan lingkungan keberlanjutan saat ini. Kampung Cengkuk adalah salah satu dari kampung-kampung pengikut tradisi Kasepuhan Ciptagelar selama ratusan tahun. Penelitian dengan menggunakan pendekatan deskriptif-kualitatif ini yang bertujuan untuk mengetahui faktor dari dalam dan luar kampung penyebab deforestasi hutan alam dengan rata-rata sekitar 6-8% per tahun. Hasil penelitian menunjukkan bahwa praktik ekoreligi masih dianut warga kampung dengan menjaga hutan tutupan (leuweung tutupan) untuk kegiatan subsistensi. Hipotesa yang dibangun adalah perubahan sosio-kultur terjadi pada masyarakat dengan membatasi kegiatan berladang di hutan tetapi lebih kepada kegiatan bertani di sawah ladang untuk mengelola lingkungan berkelanjutan. Pengurangan pada proses dan kegiatan upacara, yang semula delapan upacara daur ladang menjadi lima upacara daur sawah. Kegiatan profan lebih banyak pada pengembangan komoditas tanaman ekonomi di kebun-talun. Kata kunci: Ekoreligi, Kampung, Lingkungan, Hutan, Tradisi